How do you know when you have interoperability? - Hammond, William Ed (European Journal for Biomedical Informatics, 2018)
This paper first looks at the several definitions of the word interoperability. Next, the paper addresses several of the distinct components that are factors in accomplishing interoperability: semantic interoperability, functional interoperability, stakeholder interoperability, consumer interoperability, business interoperability, privacy and security interoperability, and international interoperability. This paper discusses each of these components in terms of their current state relating to interoperability and suggests what changes might be made to achieve interoperability.
Keywords: zdravotnické informační systémy; Health Information Systems; Data Systems; datové systémy; Health Information Interoperability; interoperabilita zdravotnických informací